2019
DOI: 10.1097/prs.0000000000005609
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Serial Measurement of Muscle Volume in TRAM Flaps Using the Eclipse Treatment Planning System

Abstract: Background: Muscle flaps used in reconstructive surgery are known to lose volume over time because of denervation and disuse atrophy. However, there is currently no agreement on a quantitative approach to evaluating volume changes. Here, long-term serial measurement of muscle volume in transverse rectus abdominis musculocutaneous (TRAM) flap breast reconstruction has been conducted using the Eclipse treatment planning system. Methods: This was a retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…When looking at the muscle:fat ratio, similar results to head and neck reconstruction were seen in TRAM flap breast reconstruction. Muscle tissue in TRAM flaps underwent a significant reduction of 70% after 15 months following the initial breast reconstruction in patients without adjuvant radiotherapy [ 77 ]. Studies evaluating the DIEP flap, often considered the workhorse flap, have reported volume losses ranging from a slight increase to a decrease of 26%, aligning with findings from adipose flaps used in head and neck reconstructive procedures [ 35 , 36 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…When looking at the muscle:fat ratio, similar results to head and neck reconstruction were seen in TRAM flap breast reconstruction. Muscle tissue in TRAM flaps underwent a significant reduction of 70% after 15 months following the initial breast reconstruction in patients without adjuvant radiotherapy [ 77 ]. Studies evaluating the DIEP flap, often considered the workhorse flap, have reported volume losses ranging from a slight increase to a decrease of 26%, aligning with findings from adipose flaps used in head and neck reconstructive procedures [ 35 , 36 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The flap volume of muscle flaps such as a transverse rectus abdominis musculocutaneous (TRAM) flap and latissimus dorsi (LD) flap decreases over time from denervation and disuse atrophy. [4][5][6][7] A recent report illustrated that the muscle of a TRAM flap lost more than 70 percent of its volume in the first 15 months and reduced to approximately 20 percent of its original size. 6 However, it is unclear whether the volume of the breast decreases or not following DIEP flap breast reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] A recent report illustrated that the muscle of a TRAM flap lost more than 70 percent of its volume in the first 15 months and reduced to $20 percent of its original size. 6 However, it is unclear whether the volume of the breast decreases or not following DIEP flap breast reconstruction. This study aimed to assess, through utilizing 3D surface imaging, whether the reconstructed breast volume changed postoperatively after a DIEP flap.…”
mentioning
confidence: 99%
“…[1][2][3] In addition, some studies have examined these volume changes in cases of pedicled flaps rather than free flaps. 4,5 Muscle or myocutaneous (MC) flaps were used often in the past, and reinnervation was usually not performed, because the muscle was only used to fill the volume. In case of breast reconstruction using the latissimus dorsi muscle, denervation was performed to prevent animation deformity.…”
mentioning
confidence: 99%
“…Several studies have reported flap volume changes after free tissue transfer 1–3 . In addition, some studies have examined these volume changes in cases of pedicled flaps rather than free flaps 4,5 . Muscle or myocutaneous (MC) flaps were used often in the past, and reinnervation was usually not performed, because the muscle was only used to fill the volume.…”
mentioning
confidence: 99%